Aplikasi Dosis Mikoriza Campuran(Glomus mosseae dan Gigaspora sp.) terhadap Pertumbuhan dan Hasil Beberapa varietas Tanaman Cabai Pada Tanah Andisol Kabupaten Bener Meriah - Maulana Zubir; Rahmat Barona; Aris Zaputra; Aprianty (Journal Agro-Livestock, 2025)
This study aims to determine the dose of mixed mycorrhizae (Glomus mosseae and Gigaspora sp.) on the growth and yield of several chili plants on Andisol soil in Bener Meriah Regency. This research was conducted at the Experimental Garden, Greenhouse and Plant Physiology Laboratory, Faculty of Agriculture, Syiah Kuala University which took place from May to September 2024. The design used in this study was a 4 x 3 factorial Randomized Block Design with 3 replications consisting of 2 series so that 72 experimental units were obtained. The factors studied were the mycorrhizal dose (D) and chili varieties (V). The mycorrhizal dose consists of 4 levels, namely; 0 g/plant, 5 g/plant, 10 g/plant and 15 g/plant. The variety factor consists of 3 levels, namely: FARUX variety, SIOS TAVI F1 variety and LADO F1 variety. Parameters observed were plant height, stem diameter, number of productive branches, plant wet weight, plant dry weight, root wet weight, root dry weight, number of fruits, fruit weight, fruit length and yield potential and root infection. The results showed that the best mixed mycorrhizal dose treatment for growth and yield parameters was 10 g/plant. The best variety for growth and yield was SIOS TAVI F1.